Effects of sphingomyelin/ceramide ratio on the permeability and microstructure of model stratum corneum lipid membranes - Pullmannová, Petra; Staňková, Klára; Pospíšilová, Markéta; Skolová, Barbora; Zbytovská, Jarmila; Vávrová, Kateřina (Biochimica et biophysica acta, 2014)
The conversion of sphingomyelin (SM) to a ceramide (Cer) by acid sphingomyelinase (aSMase) is an important event in skin barrier development. A deficiency in aSMase in diseases such as Niemann-Pick disease and atopic dermatitis coincides with impaired skin barrier recovery after disruption. We studied how an increased SM/Cer ratio influences the barrier function and microstructure of model stratum corneum (SC) lipid membranes. In the membranes composed of isolated human SC Cer (hCer)/cholesterol/free fatty acids/cholesteryl sulfate, partial or full replacement of hCer by SM increased water loss. Partial replacement of 25% and 50% of hCer by SM also increased the membrane permeability to theophylline and alternating electric current, while a higher SM content either did not alter or even decreased the membrane permeability. In contrast, in a simple membrane model with only one type of Cer (nonhydroxyacyl sphingosine, CerNS), an increased SM/Cer ratio provided a similar or better barrier against the permeation of various markers. X-ray powder diffraction revealed that the replacement of hCer by SM interferes with the formation of the long periodicity lamellar phase with a repeat distance of d=12.7nm. Our results suggest that SM-to-Cer processing in the human epidermis is essential for preventing excessive water loss, while the permeability barrier to exogenous compounds is less sensitive to the presence of sphingomyelin.
Keywords: Cholesterol; Lipid Bilayers; epidermis; Chromatography, High Pressure Liquid; Cell Membrane Permeability; kůže; ceramidy; Sphingomyelins; Ceramide; Humans; difrakce rentgenového záření; Skin; X-Ray Diffraction; Sphingomyelin; cholesterol; Female; kyseliny mastné neesterifikované; Permeability; membránové lipidy; ženské pohlaví; lipidové dvojvrstvy; X-ray diffraction; Fatty Acids, Nonesterified; Membrane Lipids; permeabilita buněčné membrány; Stratum corneum model; Ceramides; lidé; sfingomyeliny; vysokoúčinná kapalinová chromatografie; Epidermis; Lipid membrane